Exploring employees' perceptions, job-related attitudes and characteristics during a planned organizational change - Kleanthis K. Katsaros; Athanasios N. Tsirikas; Sofia-Maria N. Bani (International Journal of Business Science & Applied Management (IJBSAM), 2014)
The current study explores employee perceptions regarding organizational readiness to change, supervisory support, trust in management and appropriateness of change during a planned organizational change in a public hospital. Survey data were collected at two time periods, before and five months after the initiation of the planned change. Research findings show a significant increase in perceptive organizational readiness to change, supervisory support, trust in management and appropriateness of change after the planned change implementation. Findings also suggest that differences in the aforementioned perceptions are moderated by certain job-related attitudes, namely, job satisfaction, organizational commitment and job involvement; and job-related characteristics, namely, skill variety, task identity, task significance feedback, autonomy and goal clarity. Theoretical and practical implications of these findings are discussed.
Keywords: 650; attitudes; job characteristics; perceptions; organizational change